GASTROESOPHAGEAL CANCER: CLINICAL PATHOGENETIC APPROACHES TO NUTRITIVE SUPPORT IN THE PERIOPERATIVE PERIOD - О. P. Bobrova; R. А. Zukov; Yu. A. Dikhno; A. A. Моdestov (Сибирский онкологический журнал, 2016)
The review is devoted to clinical pathogenetic mechanisms of the trofologic status disorder in patients with gastroesophageal cancer (GEС). The current approaches to nutritive support in the perioperative period for patients with GEС have been presented.